Knowledge and awareness of asbestos risk among General Practitioners: Validation of a questionnaire in an area with a high incidence of asbestos-related diseases - Marinella Bertolotti; Manuela Tamburro; Angelo Salzo; Antonella Cassinari; Stefania Crivellari; Carlotta Bertolina; Marianna Farotto; Carmen Adesso; Michela Anna Di Palma; Anna Natale; Federico Torregiani; Guglielmo Pacileo; et al. (Preventive Medicine Reports)
Objective: Given the critical role of general practitioners (GPs) in the early diagnosis and management of asbestos-related diseases (ARDs), and the significant history of asbestos fibres pollution in Alessandria Local Health Authority (ASL AL), this project aimed to assess the knowledge and awareness of asbestos risks, as well as the experience in diagnosing ARDs among GPs working in Alessandria province, Northern Italy. Methods: A questionnaire was administered to 216 GPs from all ASL AL territorial districts during 26 Territorial Assistance Equipes (EATs) meetings, held from September 2022 to January 2023. It contained 29 questions covering three main areas: ‘knowledge and awareness’, ‘competence and experience’, ‘sociodemographic characteristics and workload’. Results: Although GPs were aware of the health hazards of asbestos (94 %) and the increased risk of mesothelioma from asbestos exposure (92.6 %), significant disparities and heterogeneity of knowledge were observed among territorial districts and by comparing Casale Monferrato district with all the others, particularly regarding asbestos exposure routes, reporting of occupational diseases, and mesothelioma latency. Conclusions: This project provides a comprehensive overview of GPs' knowledge, awareness and experience in managing ARDs, providing indications of customised training requirements. This evaluation could be extended to all areas with a history of previous asbestos exposure and provide a useful tool for policy makers to define and plan strategic actions on asbestos. This work could also be adapted to different realities with a history of environmental pollutant exposure other than asbestos, which pose a risk for the development of several diseases.